2021
DOI: 10.1111/jnc.15567
|View full text |Cite|
|
Sign up to set email alerts
|

E3 ubiquitin ligase Nedd4‐2 exerts neuroprotective effects during endoplasmic reticulum stress

Abstract: The neural precursor cell expressed developmentally down‐regulated protein 4‐like (Nedd4‐2) is an E3 ubiquitin ligase critical for neurodevelopment and homeostasis of neural circuit excitability. While dysregulation of Nedd4‐2 has been linked to elevated seizure susceptibility through impaired ubiquitination of multiple direct substrates, it remains largely unclear whether Nedd4‐2 interconnects other cellular pathways that affect neuronal activity and seizure susceptibility. Here, we first showed that Nedd4‐2 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 39 publications
0
6
0
Order By: Relevance
“…NEDD4-2 seemed to take part in both UPR machineries: degradation of unfolded proteins through autophagy ( Wang et al, 2016 ) and translational suppression through association with ribosomal proteins ( Eagleman et al, 2021 ). NEDD4-2 was recently reported to integrate the ER stress response to modulate seizure susceptibility ( Lodes et al, 2022 ). We also found the changes in ER protein processing pathway in the proteomic analysis of Nedd4-2 +/− mice with increased seizure susceptibility ( Liu et al, 2021 ).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…NEDD4-2 seemed to take part in both UPR machineries: degradation of unfolded proteins through autophagy ( Wang et al, 2016 ) and translational suppression through association with ribosomal proteins ( Eagleman et al, 2021 ). NEDD4-2 was recently reported to integrate the ER stress response to modulate seizure susceptibility ( Lodes et al, 2022 ). We also found the changes in ER protein processing pathway in the proteomic analysis of Nedd4-2 +/− mice with increased seizure susceptibility ( Liu et al, 2021 ).…”
Section: Discussionmentioning
confidence: 99%
“…ER stress caused could upregulate hepatic Nedd4-2 to induce an autophagic response to clear unfolded proteins ( Wang et al, 2016 ). Recently, neuronal Nedd4-2 was found to elicit ER stress-associated translational suppression through interaction with ribosomal proteins and to modulate seizure susceptibility by integrating the ER stress responses ( Eagleman et al, 2021 ; Lodes et al, 2022 ). These studies indicated a protective role of Nedd4-2 in relieving ER stress and seizures besides direct ubiquitination of neuroactive substrates.…”
Section: Introductionmentioning
confidence: 99%
“…Lentiviral transduction was performed on DIV 9 (Origene; PSD-95 lentiviral particle #RC215178L4V; control lentiviral particle #PS100093V). For the synapse counting experiment, coverslips were prepared as described previously (Lodes et al, 2022 ). Briefly, cells were washed with phosphate-buffered saline (PBS) once, fixed with fixation buffer (4% paraformaldehyde and 4% sucrose in PBS) for 15 min, and then permeabilized with permeabilization buffer (0.2% Triton X-100 in PBS) for 10 min.…”
Section: Methodsmentioning
confidence: 99%
“…G* power was used to perform power analysis. Expected effect sizes were based on our previously published studies (Eagleman et al, 2021; Lodes et al, 2021). Sample sizes for western blot, MEA recording, and immunocytochemistry were equal or greater than the suggested size of 4, 6, and 11, respectively, for a power of 0.8 and a Type I error (alpha) of 0.05.…”
Section: Methodsmentioning
confidence: 99%